Design and characterisation of cellular composite structures for automotive crash-boxes manufactured by out of die ultraviolet cured pultrusion. (1st March 2019) - Saenz-Dominguez, I.; Tena, I.; Esnaola, A.; Sarrionandia, M.; Torre, J.; Aurrekoetxea, J.
Abstract: The present paper analyses the feasibility of designing a honeycomb-like crash-box, as a cellular structure, based on data obtained from the characterisation of the building block. In order to generalise the conclusions of the study, different thicknesses and testing velocities have been analysed. The main conclusion is that, if the same thickness and testing velocity are used, the specific energy absorption ( SEA ) and peak load values are similar for the building block and the crash-box. Consequently, the design of the complex structure can be validated by simplifying the test procedure. However, special attention must be put on the testing velocity, since the broken fibre percentage is higher in quasi-static conditions. Thus, SEA in quasi-static conditions is higher than in dynamic conditions, 64 kJ/kg and 45 kJ/kg respectively.